P146 Dysplasia Surveillance in inflammatory bowel disease—a cohort study. (25th January 2019) - Saraiva, S; Rosa, I; Moleiro, J; Pereira da Silva, J; Fonseca, R; Dias Pereira, A
Abstract: Background: Patients with inflammatory bowel disease (IBD) are at increased risk for developing colorectal cancer (CRC). Currently, surveillance colonoscopy is recommended to detect and treat neoplastic lesions. Methods: A cohort study was conducted to determine clinical and endoscopic variables associated with dysplasia in IBD patients who were part of a colonoscopy surveillance programme between 2011 and 2016. Results: In total, 162 patients (51.2% men, mean age at diagnosis 36.8 ± 13.5 years, mean duration of IBD at the start of the Programme: 11.0 ± 8.9 years) were included. 105 patients had ulcerative colitis (UC) and 57 had Crohn's Disease (CD). Six patients had concurrent primary sclerosing cholangitis (PSC), 18 had a family history of CRC and 6 had personal history of colorectal dysplastic lesions. 342 colonoscopies were performed during the 5 years period (2.1 ± 1.2 colonoscopies/patient). Random biopsies were performed at least once in 81.5% of patients with a mean 27.5 ± 6.4 biopsy samples per colonoscopy and 33.3% of the patients underwent chromoendoscopy (CE) at least once. Endoscopically resectable lesions were detected in 55 patients (34%) and visible lesions deemed unfit for endoscopic resection were found in 5 patients (3.1%). Overall, 61 dysplastic visible lesions (58 with low-grade dysplasia and 3 with high-grade dysplasia) and 1 adenocarcinoma were found in 34 patients. Dysplasia in random biopsies was present in 3 patients, the yield of random biopsies for dysplasia being 1.85% per-patient (3/162), 1.75% per-colonoscopy (6/342) and 0.25% per-biopsy (9/3637). Dysplasia detected in random biopsies was associated with a personal history of visible dysplasia ( p = 0.006). The presence of dysplasia, either in targeted samples or random biopsies, was significantly associated, on univariate analysis, with type of IBD (26.7% in UC vs. 10.5% in CD) ( p = 0.016), with the performance of random biopsies ( p = 0.009), and CE ( p = 0.05) and with previous ileo-colonic surgeries ( p = 0.002). On multi-variate analysis, dysplasia was associated with type of IBD ( p = 0.034), with the performance of random biopsies ( p = 0.09) and with previous ileo-colonic surgeries ( p = 0.001). Median disease duration was superior in patients with dysplasia compared with those without dysplasia (14.0 (IQR 5.75–21.0) vs. 9.0 (IQR 3.25–15.0) years, p = 0.03). There was no significant association between the presence of dysplasia and family history of CCR or personal history of PSC. Conclusions: Our data confirm that patients with longstanding IBD, in particular UC, should be enrolled in dysplasia surveillance Programmes and that performing CE and random biopsies helps in the detection of colonic neoplastic lesions.